The Responsiveness of Hong Kong Private Residential Housing Prices - Lam, Kwok-Chiu (International Journal of Economics and Financial Issues, 2016)
Long-run equilibrium house price is determined by demand and supply factors. On the demand side, previous studies on housing prices often use gross domestic product (GDP) and population or GDP per capita as purported driver(s), yet little attention has been paid to the role of households. On the supply side, using land supply or new unit completions and construction cost as inherited factors is most common. In this article, we rely on a reducedform ordinary least squares equation encompassing selected demand and supply fundamentals to explain Hong Kong private residential house price movements. We aim to: (i) Evaluate the superiority of GDP per household versus GDP per capita, and (ii) assess the relative price responsiveness to various factors like interest rate and mortgage lending across different submarkets. From our investigation, no conclusive evidence can be drawn on (i). Regarding (ii), we find that while larger-sized units are invulnerable to interest rate movements, on geographical area basis, higher interest rate sensitivity tends to accompany lower population density. Moreover, larger-sized units and those located at Hong Kong Island are more responsive to the overall economic conditions (i.e., GDP). Lastly, we point out that in view of the potential threats in 2015, more downward pressure will be exerted on house prices. Keywords: Gross Domestic Product, Household, Population, Hong Kong, House Price Responsiveness JEL Classifications: E43, R31